2018
DOI: 10.1090/mcom/3379
|View full text |Cite
|
Sign up to set email alerts
|

Finite element approximation of steady flows of generalized Newtonian fluids with concentration-dependent power-law index

Abstract: We consider a system of nonlinear partial differential equations describing the motion of an incompressible chemically reacting generalized Newtonian fluid in three space dimensions. The governing system consists of a steady convection-diffusion equation for the concentration and a generalized steady power-law-type fluid flow model for the velocity and the pressure, where the viscosity depends on both the shear-rate and the concentration through a concentration-dependent power-law index. The aim of the paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In Section 2 we introduce the necessary notations, state some auxiliary results, and define the weak formulation of the problem. Then, in Section 3 we prove the uniqueness of the steady state to an incompressible chemically reacting fluid flow problem under more restrictive assumptions than those under which existence of weak solutions was shown in [26][27][28]30]. Furthermore, it will be shown that the uniqueness result can be applied to a model of the synovial fluid.…”
Section: Outline Of the Papermentioning
confidence: 93%
See 2 more Smart Citations
“…In Section 2 we introduce the necessary notations, state some auxiliary results, and define the weak formulation of the problem. Then, in Section 3 we prove the uniqueness of the steady state to an incompressible chemically reacting fluid flow problem under more restrictive assumptions than those under which existence of weak solutions was shown in [26][27][28]30]. Furthermore, it will be shown that the uniqueness result can be applied to a model of the synovial fluid.…”
Section: Outline Of the Papermentioning
confidence: 93%
“…Remark 1. Compared to the works [25][26][27][28]30], we imposed slightly stronger conditions on the stress tensor S. Most notably, by assuming (implicitly) an infinite shear plateau for the viscosity (cf. the paragraph following ( 44)), we circumvent the difficulty of dealing with Lebesgue and Sobolev spaces with variable exponents.…”
Section: S(c κ)mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in [16] and [43], optimal error estimates for shear thinning non-Newtonian fluids have been addressed, whereas in [61] a finite element method based on a four-field formulation of the nonlinear Stokes equations has been considered. Moreover, without aiming at completeness, we refer to the book [41] and the references therein, and to [29,36,46,47] as recent relevant contributions on the numerical discretization of generalized Stokes problems. We also point out that the approximation of steady isothermal non-Newtonian incompressible Stokes fluid problems on polytopal meshes have been addressed in [19].…”
Section: Introductionmentioning
confidence: 99%
“…We refer to [21,22,49,25,26,20] to name a few. In addition, the convergence analysis for the p-Navier-Stokes problem using FE methods can be found in [29,41,39,40,33]. On the other hand, to the best of the authors knowledge, there are no investigations using DG methods for the p-Navier-Stokes problem (1.1).…”
mentioning
confidence: 99%